Women Political Leaders in Rwanda and South Africa : Narratives of Triumph and Loss - Morojele, Naleli Mpho Soledad (2016)
Narratives of Triumph and Loss explores the successes, challenges and controversies of women‘s post-conflict political leadership. Through interviews with women who have held significant leadership positions, the book explores the relationships between their educational, professional, activist and personal backgrounds. It situates their stories within historical and contemporary political contexts, illustrating the gendered ways in which women experience politics as citizens and politicians.